Expression of Adipocyte Binding Protein-2 (AP-2) on the Adipogenic Differentiation of Mesenchymal Stem Cell after Pulsed Electromagnetic Field (PEMF) Exposure - Umiatin U (Journal of Global Pharma Technology, 2020)
Obesity is a health condition that can cause serious health problems in developing countries such as Indonesia and still a major health concern worldwide. Obesity increasing the risk of a number of pathological disorders including certain cancers, heart disease, stroke, and diabetes. It has been reported that Pulsed Electromagnetic Field (PEMF) have an inhibitory effect on adipogenesis of MSCs. However, it is not clear if this effect is direct or indirect. Various genes are involved in the development of obesity include adipocyte binding protein 2 (AP-2) which is associated with inflammation and the metabolic syndrome. In the present study, we investigated the effect of PEMF exposure with frequency 75 Hz and magnetic field 2 mT on the adipogenic differentiation of mesenchymal stem cells (MSCs). In the present study we used the MSCs second passage. The cells were stimulated by PEMF of 75 Hz/2mT for 14 days 10 in/day. The relative expression of AP-2 was measured on days 2, 4, 7 and 14 by using quantitative reverse transcription polymerase chain reaction (qRT-PCR) method. The PEMF significantly inhibited adipogenic differentiation by down regulating the expression of AP-2 on days 2, 4 and 7. This result indicated that PEMF exposure may have potent effect to inhibit adipogenic differentiation. Keywords: Pulsed electromagnetic field, Adipogenic, Mesenchymal Stem Cells, AP-2